Microwave performance of thin-film technologies on LTCC - Fund, Andrew (Kansas State University, 2015)
At RF frequencies and beyond, metallic circuit interconnects no longer behave as lumped-element wires; instead they exhibit distributed-element behavior and are classified as transmission lines. Power losses on transmission lines are of great concern to RF and microwave engineers and great care is taken to minimize power losses while still maintaining application-based robustness. The combination of low-temperature co-fire ceramics (LTCCs) and thin-film transmission line fabrication allows application-specific robustness and excellent microwave and millimeter wave performance to be achieved. LTCC technology provides a low-loss microwave substrate and allows for thin-film metal and insulator depositions to form precision transmission-line geometries and surface-applique capacitors. In the field of thin-film metals however, concern over excess power losses at high frequencies has arisen due to the necessity of a high-resistance metallic adhesion layer which is required for the mechanical adhesion of the transmission lines to the LTCC substrate. This is especially worrisome in a microstrip configuration where the current density is concentrated at the substrate-metal interface; exactly where the high-loss metal is situated. This thesis shows that if the high-resistance adhesion layer is limited to a thickness which is a fraction of its skin depth, with more conductive metals layered above, then those excessive resistive losses can be avoided. Issues with decreasing the total thickness of the thin-film layered metals are also investigated to achieve better interconnect line-and-space resolution, which is required for electronics operating at millimeter-wave bandwidths. Several test cases show that thinning of the metal layers has minimal impact on electrical performance. However, poor signal integrity is observed when the finished thickness of the metal stack up is reduced below 1μm. Further testing reveals that surface roughness leads to manufacturing issues when trying to produce thin-films with thicknesses in the sub-micron range. Finally, a novel bypass and coupling capacitor topology is proposed and investigated. The capacitors are simple thin-film metal-insulator-metal constructions designed for use in a flip-chip mounting environment. Testing shows the capacitors exhibit a very low impedance through 20 GHz making them an ideal board-level bypass solution. This technology has the potential to replace all but the large bulk charge storage capacitors in electronic designs, increasing performance and mechanical robustness, while simultaneously decreasing bill of material cost and PCB assembly times.
Keywords: Microstrip; Thin-film; Adhesion layer; Microwave; Low temperature co-fire ceramic; Capacitor; Electrical Engineering (0544)